Penerapan Metode Diskusi Kelompok untuk Meningkatkan Pemahaman Siswa terhadap Materi Pendidikan Agama Islam di SMA PAB 4 Sampali - Indah Permata Sari; Mario Kasduri (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to examine the implementation of the group discussion method to improve students’ understanding of Islamic Religious Education material at SMA PAB 4 Sampali. The background of this research arises from the low level of student participation in conventional teacher-centered learning, which results in poor conceptual understanding. This study uses a qualitative approach with a descriptive method. The research subjects were eleventh-grade students taking Islamic Religious Education lessons. Data collection techniques included observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the application of the group discussion method successfully increased students’ active participation, both in expressing opinions and listening to classmates’ ideas. Furthermore, group discussions created a collaborative learning atmosphere, allowing students to complement each other’s understanding of the material. Students’ learning outcomes improved, as evidenced by higher evaluation scores compared to before the method was applied. Therefore, the group discussion method can be an effective alternative learning strategy for Islamic Religious Education subjects.